Semiochemical delivery systems based on natural polymers to attract sand flies (Diptera: Psychodidae) - Bueno, Ana Carolina [UNESP]; Machado, Vicente Estevam [UNESP]; da Rocha Silva, Flávia Benini [UNESP]; Boni, Fernanda Isadora [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Gremião, Maria Palmira Daflon [UNESP]; Pinto, Mara Cristina [UNESP] (Springer Nature, 2023)
Background: The successful use of semiochemicals to attract insects to traps is based on research on the most suitable compounds and their release profiles over time. Based on the group's promising results, matrices with a more adequate release profile and more eco-friendly properties for the release of 1-hexanol were developed. To use a more suitable prototype in the field, the most promising systems were added to a capsule and evaluated in a wind tunnel. Behavioral experiments were performed using the sand fly species, Lutzomyia longipalpis, to evaluate the efficacy of the proposed system. Methods: Different delivery systems were developed by varying the polymer (gellan gum and pectin) ratio, crosslinker (aluminum chloride) concentration, and glutaraldehyde removal.The delivery systems were loaded with 1-hexanol, and their release profiles were evaluated using gravimetric analysis under ambient and high-humidity conditions. When the matrix system was placed inside a plastic container, modulations in the active release profile were observed and the system could be reused. Actid attraction behaviors of the sand fly species, Lu. longipalpis, were evaluated in a wind tunnel when exposed to 1-hexanol-loaded release systems at different times. Results: Among the four formulations evaluated, System 2 (gellan gum and pectin in a 1:1 ratio with 5% aluminum chloride) exhibited the most promising release profile, with greater uniformity and longer compound release time. The maximum 1-hexanol release uniformity was achieved over a longer time, mainly every 24 h, under both ambient and high-humidity conditions. System 2 can be reused at least once with the same structure. The wind tunnel trials exhibited efficient activation and attraction of Lu. longipalpis to 1-hexanol after 24, 48, and 72 h in System 2 placed inside the capsules. Conclusions: The polymeric matrix supplemented with 1-hexanol and introduced in plastic capsules showed promising results in attracting sand flies. This system can be used as a solution for other attractive compounds as well as in other applications where their release needs to be controlled or prolonged. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: 1-hexanol; Attractiveness; Kairomones; Lutzomyia longipalpis; Release systems